Disentangling Subject and Anacoluthon NPs in Topic: A Cognitive Grammar and Gestalt Psychology based approach - Lima e Silva, Luis Filipe; Rodrigues de Paula, Ronaldo (SOLETRAS, 2021)
In this paper we analyze NPs in Topic which can be either the subject of the verb in Comment, or autonomous items usually called anacolutha. It explores how these different NPs are mapped according to spontaneous speech data. Departing from Langacker's proposal (2001), in which the Topic and the subject act as trajectors of different scopes, it is argued that such a concept is adequate to the empirical data, since it allows the possibility of co-occurrence and intertwining of both categories in speech. In addition, we also investigated the difference in the cognitive processing of subject and anacoluthon NPs in Topic building upon the concepts of baseline and elaboration (LANGACKER, 2016). As the concepts of subject and Topic in the approach of Cognitive Grammar derive, in part, from the Gestalt psychology notions of Figure and Ground, the anacoluthon in Topic can be referred to as the Figure and the illocutionary force of the Comment would be the Ground. The only difference in relation to the visual elements is that, since they displaces through the space axis, the Figure and the Ground can be inverted depending on where the focus of attention is turned. However, as the speech is unfolded along the time axis, reversion is not possible, in such a way that an Anacoluthon in Topic will always be the Figure and the Comment will always be the Ground.